2023
DOI: 10.1039/d2lc00799a
|View full text |Cite
|
Sign up to set email alerts
|

Nanoparticle protein corona: from structure and function to therapeutic targeting

Abstract: Representation of the influence of biological and nanoscale factors on protein corona conformation and function in a healthy versus a pathogenic biological environment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
41
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(54 citation statements)
references
References 273 publications
0
41
0
Order By: Relevance
“…Alternatively, the adsorption of plasma apolipoprotein E (ApoE) can guide LNPs uptake toward hepatocytes through interaction with the low-density lipoprotein receptor (LDLR). As previously mentioned, active targeting through antibody-receptor interactions may redirect LNPs to desired tissues and cells depending on both the specific formulation of the Ab-LNPs and its interactions with serum proteins. , …”
Section: In Vivo Fate Of Ab-lnpsmentioning
confidence: 99%
See 1 more Smart Citation
“…Alternatively, the adsorption of plasma apolipoprotein E (ApoE) can guide LNPs uptake toward hepatocytes through interaction with the low-density lipoprotein receptor (LDLR). As previously mentioned, active targeting through antibody-receptor interactions may redirect LNPs to desired tissues and cells depending on both the specific formulation of the Ab-LNPs and its interactions with serum proteins. , …”
Section: In Vivo Fate Of Ab-lnpsmentioning
confidence: 99%
“…As previously mentioned, active targeting through antibodyreceptor interactions may redirect LNPs to desired tissues and cells depending on both the specific formulation of the Ab-LNPs and its interactions with serum proteins. 101,102 The biodistribution and tissue tropism of each LNP formulation are unique, determined by their inherent size, surface charge, protein corona, and lipid structures. 103 Typically, liposomes and LNPs are rapidly cleared from the blood after intravenous injection.…”
Section: In Vivo Fate Of Ab-lnpsmentioning
confidence: 99%
“…The type of polymer and the coating technique used need to be carefully selected as they inevitably alter the physiochemical properties of the NPs’ surface and, subsequently, thus, their biological fate. Recent studies on inorganic NPs have shown that the size and shape of the NPs, their surface chemistry, and other physical properties affect the biological interaction within seconds of being in contact with biological fluids such as blood or protein-supplemented cell growth media . A majority of the NPs are covered by proteins, which ultimately influence the NP–cell association, cytotoxicity, biodistribution, and tumor targeting ability. Despite the significant interest vested in the correlation between polymer properties and biological activity in vitro and in vivo, little attention has been given to the changes in the polymer structure caused by the presence of drugs .…”
Section: Introductionmentioning
confidence: 99%
“…The initial soft corona is short‐lived, the macromolecular‐proteins are exchanged by high‐affinity macromolecular‐proteins to form a nanoparticle‐protein complex, referred to as hard corona as shown in Figure 1 20 . The latter binds to receptors situated on the surface of phagocytic cells trailed by internalization and digestion by lysozymes 21 . Silvia et al studied the effects of serum protein transferrin to sulfonate polystyrene nanoparticles at different concentrations, ranging from 0.5 to 40 μg/mL to understand the interaction between nanoparticles and micromolecular‐opsonins using florescence correlation spectroscopy (FCS).…”
Section: Introductionmentioning
confidence: 99%
“…20 The latter binds to receptors situated on the surface of phagocytic cells trailed by internalization and digestion by lysozymes. 21 Silvia et al studied the effects of serum protein transferrin to sulfonate polystyrene nanoparticles at different concentrations, ranging from 0.5 to 40 μg/mL to understand the interaction between nanoparticles and micromolecular-opsonins using florescence correlation spectroscopy (FCS). The system showed the formation of irreversibly bound monolayer (hard corona) due to strong covalent bonds between transferrin and polystyrene nanoparticles.…”
mentioning
confidence: 99%